Heart-targeted adeno-associated viral vectors selected by in vivo biopanning of a random viral display peptide library - Ying, Ying; Müller, Oliver J.; Göhringer, Caroline; Leuchs, Barbara; Trepel, M.; Katus, Hugo; Kleinschmidt, Jürgen (Gene therapy, 2010)
Selection of targeted vectors from virus display peptide libraries is a versatile and efficient approach to improve vector specificity and efficiency. This strategy has been used to target various cell types in vitro. Here, we report the screening of an adeno-associated virus type 2 (AAV2) display peptide library in vivo to select vectors specifically homing to heart tissue after systemic application in mice. Selected library clones indicated superior specificity of gene transfer compared with wild-type AAV2, AAV9 and a heparin binding-deficient AAV2 mutant. Such targeted vectors were able to reconstitute expression of δ-sarcoglycan in the heart of adult δ-sarcoglycan knockout mice after systemic gene transfer in vivo, attesting to the therapeutic potential of this approach.